Are Sufficient Statistics Necessary? Nonparametric Measurement of Deadweight Loss from Unemployment Insurance - David S. Lee; Pauline Leung; Christopher J. O'Leary; Zhuan Pei; Simon Quach (Institute of Labor Economics (IZA), 2019)
Central to the welfare analysis of income transfer programs is the deadweight loss associated with possible reforms. To aid analytical tractability, its measurement typically requires specifying a simplified model of behavior. We employ a complementary "decomposition" approach that compares the behavioral and mechanical components of a policy's total impact on the government budget to study the deadweight loss of two unemployment insurance policies. Experimental and quasi-experimental estimates using state administrative data show that increasing the weekly benefit is more efficient (with a fiscal externality of 53 cents per dollar of mechanical transferred income) than reducing the program's implicit earnings tax.
Keywords: C14; C20; C31; H2; H23; J64; J65; J68; 330; behavioral and mechanical effects; decomposition; sufficient statistics; optimal unemployment insurance; partial unemployment insurance; unemployment insurance; regression kink design; deadweight loss; fiscal externality